The Strategy of Developing Kambang Iwak in Palembang Tourism Object as Tourist Destination in Palembang City - Novita Sari; Nurlista Iryanti; Nyimas Maynisa Aulia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Kambang Iwak is one of the city parks with great potential to be developed as a tourist destination in Palembang City. As one of the most visited public spaces in Palembang, Kambang Iwak has the potential to become an attractive tourist destination for local and international visitors. This study aims to analyze the strategy for developing Kambang Iwak as a tourist destination in Palembang by utilizing its existing potential. The research was conducted from July to August 2025. Using a qualitative method with a Supriyono approach. The Supriyono approach was used because it provides a systematic framework for analyzing tourism development strategies, identifying local potentials, and understanding the relationship between management, community participation, and tourism sustainability. Data were collected through three main activities: (1) direct field observations, (2) interviews with relevant parties such as vendors, tourists, and managers, and (3) documentation of activities around Kambang Iwak. The collected data were analyzed using qualitative methods to understand the effective strategies that can be applied in developing Kambang Iwak as an attractive destination for both local and international tourists. Based on the research results, development strategies focus on improving facilities, promoting tourism, and sustainable environmental management. By enhancing infrastructure, improving service quality, and promoting local attractions, Kambang Iwak is expected to become a more competitive and tourist-friendly destination.